IgE Antibody Measurements in Ragweed Hay Fever RELATIONSHIP TO CLINICAL SEVERITY AND THE RESULTS OF IMMUNOTHERAPY - Lichtenstein, L. M. (1973)
Specific IgE anti-ragweed antibodies (IgEAR) were measured over two years in two groups of highly sensitive patients treated (immunized) with either ragweed extract or placebo and in a third group of placebo-treated, relatively insensitive patients. The IgEAR on the patients' basophils were assessed by ragweed antigen E (AgE)-induced histamine release; blocking (IgG) antibodies were measured by their ability to inhibit AgE induced histamine release. These data were evaluated against the clinical severity of ragweed hay fever in each patient. We found that: (a) In placebo treated patients IgEAR usually declined gradually prior to the ragweed season and were boosted by environmental exposure to ragweed pollen. (b) In immunized patients the IgEAR rose at the beginning of treatment, but fell as immunotherapy proceeded; by the end of the second year the levels had decreased in 18/19 patients. (c) The increase in blocking antibody during immunotherapy correlated significantly (P < 0.05) with the decrease in serum IgEAR. (d) Judged by their sensitivity to AgE induced histamine release, IgEAR on basophils correlated significantly with IgEAR in the serum of untreated patients (P < 0.01). (e) The highly sensitive placebo treated patients' symptom scores were significantly correlated with their IgEAR in serum (P < 0.01) and with the sensitivity of their basophils to AgE-induced histamine release (P < 0.01). Neither correlation was observed in the relatively insensitive patients. (f) In the treated group the IgEAR measurements predicted neither the degree of their illness nor their clinical improvement We conclude tha IgE antibody measurements may be useful in the assessment of the severity of reaginic allergy in highly sensitive patients. Its use in modestly sensitive patients requires patients requires further study, as does the inverse association between IgE and IgG antiragweed antibodies.